Teaching English for Specific Purposes (ESP) to the Students in English Language Teaching (ELT) - Fitria, Tira Nur (Universitas PGRI Adi Buana Surabaya, 2020)
This article will provide 1) general overview and aniani4d course design of English for Specific Purposes in the field of ELT (English Language Teaching), 2) the role of teacher and student in English for Specific Purposes (ESP), and 3) the difficulties related to teacher, student, environment and others in teaching English bolawins for Specific Purposes (ESP). In the kamislot field of English Language Teaching (ELT), English for Specific Purposes (ESP) concerns the specific English language needs of the target learners/students bolawins. It refers to teaching a specific genre of English for students with specific hagoslot goals which is oriented and focused on English teaching and learning. ESP is designed and developed based on an assessment of purposes and needs and the wede168 activities for which English is needed. There are many teacher’s roles, such as asking to organize courses, setting the learning objectives, establishing a positive learning environment and evaluating the students' progress. While, the learners are related to a specific interest in learning, subject matter knowledge, and well-built learning strategies. In the implementation of ELT, there are any difficulties or problems related to the teacher in teaching ESP, such as the low quality of lectures and textbooks, teachers’ improper qualification and teaching methods and lack of a theoretical framework of teaching ESP. Difficulties related to the students, such as demographic characteristics and demands of learning ESP, English proficiency, differences between different languages, lack of vocabulary, depending on the dictionary and lack of skills in using dictionary especially ESP terms. While, the difficulties related to the environment and others are lack of teaching materials, classes with a too large student number, and heavily focused on the examination.